Research trends and frontiers of groundwater-lake interaction - Zesen YANG; Jingjing LIN; Qixin CHANG; Aiguo ZHOU; Xiaolong HUANG (地质科技通报)
Significance To analyze the research trends and frontiers in the field of groundwater-lake interaction, we conducted a comprehensive review the relevant papers from the Web of Science (WOS) database. Using VOSviewer software, we mapped the developmental trajectory of research topics in the field. Core papers from both WOS and the China National Knowledge Infrastructure (CNKI) were analyzed to systematically summarize prominent topics, research tools, and existing gaps. Based on the historical development of the field, future trends were also predicted. Progress Our analysis identified three successive developmental stages in this field, including the individualism stage, the reductionism stage, and the holism stage. Current hot research topics focus on water exchange, solute transport, and ecosystem mutual feedback mechanisms. Several key challenges remain, such as the spatiotemporal heterogeneity of groundwater-lake interactions, biogeochemical processes at the groundwater-lake interface, and the delayed impact of aquifers on lake ecological restoration. The primary research methods are stable isotopes, radioisotopes, temperature tracing, remote sensing, and numerical modelling. However, variations in data accuracy and spatial coverage continue to pose challenges for the practical application of these techniques. Conclusions and Prospects In the future, this field will enter a fourth stage characterized by big data. At this stage, it is essential to integrate diverse technological approaches, with an emphasis on using big data for high-precision monitoring to improve the characterization of dynamic groundwater-lake interactions. Additionally, multidimensional inversion models of element migration should be developed, and enhanced data mining techniques should be applied at the interface to more accurately quantify solute transport flux across the groundwater-lake interface. Finally, fostering interdisciplinary collaboration and establishing a digital ecological framework will be essential to support research on the reciprocal interactions between groundwater and lake ecosystems, promoting sustainable development and environmental protection.